From patent to patient: analysing access to innovative cancer drugs. Issue 9 (September 2020) - Sharpe, Eva; Hoey, Richard; Yap, Christina; Workman, Paul
Highlights: Cancers of high unmet need are missing out on new drugs seen for other tumours. Very few targeted drugs are coming through to the clinic for paediatric cancers. It is taking too long to deliver new drugs to patients. We need radical innovation to overcome cancer evolution and drug resistance. Abstract : Analysis of cancer drugs licensed through the European Medicines Agency (EMA) in 2000–2016 shows that the number of authorisations increased over that timeframe. The median number of licensed drugs each year rose from six for 2000–2008 to 13.5 for 2009–2016. Over 2000–2016, there were 64 drug authorisations for haematological, 15 for breast, and 12 for skin cancer, but none for oesophageal, brain, bladder, or uterine cancer. Only 6% of authorisations included a paediatric indication. The average time for a drug to progress from patent priority date to availability on the National Health Service (NHS) increased from 12.8 years for drugs first licensed in 2000–2008 to 14.0 years for those licensed in 2009–2016. There was evidence that the most innovative drugs were not being prioritised for EMA licensing and NICE approval.